2001
DOI: 10.4049/jimmunol.166.5.3377
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD16 Inhibits CR3 (CD11b/CD18)-Mediated Infection of Monocytes/Macrophages by Opsonized Primary R5 HIV-1

Abstract: We demonstrate that soluble CD16 (sCD16; soluble FcγRIII), a natural ligand of CR3, inhibits the infection of monocytes by primary R5 HIV-1 strain opsonized with serum of seronegative individuals. Inhibition of monocyte infection by sCD16 was similar to that observed with anti-CR3 mAbs, indicating that opsonized HIV may use a CR3-dependent pathway for entry in monocytic cells. Cultured human monocytes express both CR3 (CD11b/CD18) and CCR5 receptors. RANTES, the natural ligand of CCR5, inhibited infection of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
3
25
0
Order By: Relevance
“…These results demonstrate that the enhancing effect of opsonization by semen was dependent on CR3-mediated entry of opsonized virus in HT-29 cells. These data extend our previous observations on the enhancing effect of complement opsonization in serum on infection of monocytes/macrophages (14). We further observed that inhibition of infection by SDF-1 was decreased in the case of infection with opsonized virus compared with that observed with unopsonized R5-and X4-tropic viruses.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results demonstrate that the enhancing effect of opsonization by semen was dependent on CR3-mediated entry of opsonized virus in HT-29 cells. These data extend our previous observations on the enhancing effect of complement opsonization in serum on infection of monocytes/macrophages (14). We further observed that inhibition of infection by SDF-1 was decreased in the case of infection with opsonized virus compared with that observed with unopsonized R5-and X4-tropic viruses.…”
Section: Discussionsupporting
confidence: 79%
“…Semen, cervicovaginal secretions, and breast milk of HIV-1-seropositive individuals contain cell-free HIV-1 particles (2, 3) and soluble complement components (4 -9). Opsonization of HIV-1 with complement was shown to result in enhanced viral infection of T and B cell lines (10 -12), primary PBMC (13), and primary monocyte/macrophage cultures (14). Since CD11b/CD18 (complement receptor type 3 (CR3) 3 ) is expressed on the apical surface of epithelial cells as well as on dendritic cells and macrophages in the submucosa, it may be speculated that opsonization of HIV with complement is important in the early events surrounding mucosal transmission of HIV (15,16).…”
Section: Opsonization Of Hiv-1 By Semen Complement Enhances Infectionmentioning
confidence: 99%
“…We also found that productive infection was strongly inhibited by anti-CD4 mAb (data not shown), suggesting that even in CR3-mediated enhancement of productive infection CD4 plays a critical role. In other studies, inhibition by anti-CR3 mAb of monocyte infection (18,22) and partial inhibition by CD11b-specific Abs (10) of PBMC infection with HIV were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Infection of human monocytes and macrophages with HIV is greatly facilitated by opsonization of the virus with C3 fragments (5,22). To test whether infection of imMDCs by HIV is influenced by opsonization, the cells were cultured with the HIV-1 primary isolate pretreated with IgG and complement.…”
Section: Effect Of Opsonization Of Hiv By Complement On Infection Of mentioning
confidence: 99%
“…Semen, cervicovaginal secretions, and breast milk contain complement proteins that may allow viral particles to be opsonized (3)(4)(5). Opsonization of HIV-1 with complement results in enhancement of viral infection of T and B cell lines (6,7), primary PBMC (8), and primary monocytes/ macrophages (9). We have demonstrated that HIV particles activate complement in semen resulting in an ability to infect human CD4-negative epithelial cells in a complement-dependent fashion via CD11b/CD18 (CR3) (10).…”
mentioning
confidence: 99%